Penyuluhan Administratif Posyandu Melalui Pengisian Registrasi dan KMS (Kartu Menuju Sehat) - Ni Made Ayu Dwi Listya Ningsih; Nyoman Sri Manik Parasari (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2024)
Cadres play a very important role in posyandu activities as one of the monitoring activities for the nutritional status of toddlers. Good knowledge about nutrition and stunting prevention efforts will assist cadres in providing counseling to the community. However, it is not only knowledge about nutrition and stunting. Knowledge about how to fill out the registration book and KMS (Health Card) must also be understood. Where many posyandu cadres in Pitra Village do not understand enough about the procedures for filling in the KMS book (Health Card) which often results in misunderstanding of information about child growth and development. Therefore, this community service activity aims to increase the knowledge and skills of Posyandu cadres in completing registration and KMS (Health Card). The main target for this activity is posyandu cadres in the Pitra Village area, Penebel. Capacity building is carried out through three methods, namely, education, simulation, and mentoring so that cadres can directly practice the knowledge that has been given. Community service activities using education, simulation and mentoring. This method can increase the knowledge and skills of posyandu cadres in completing registration and KMS (Health Card). As a suggestion, there needs to be special training for cadres on how to provide health information through educational media and health promotion.